PELAKSANAAN PRIVATISASI : TRANSPARANSI DAN AKUNTABILITAS - Natsir, Muh. Natsir (Jurnal Analisis Bisnis Ekonomi, 2004)
Reason conduct the privatisation BUMN is to improve, repair the company performance and improve the earnings without Up lease. Transparantion is especial conditions in course of privatisasi. In context Privatisation, auction and tender is often compared to go together the storey; level transparancy, explained responbility and role hrough analogy with the parliament institute in system arrange the governance. The Tenth lesson of based on experience will assist in policy making and escertain to succeed it privatisasi.